Independent Reviewing Officers' and social workers' perceptions of children's participation in Children in Care Reviews. Issue 3 (23rd August 2019) - Diaz, Clive; Pert, Hayley; Thomas, Nigel Patrick
Abstract : Purpose: The research reported here forms part of a study of children's participation in children in care reviews and decision making in one local authority in England. The purpose of this paper is to outline the views of 11 social workers and 8 Independent Reviewing Officers (IROs) and explores their perceptions of children's participation in reviews. The paper considers the barriers to young people participating meaningfully in decision making and how practice could be improved in this vital area so that children's voices are more clearly heard and when possible acted upon by professionals. Design/methodology/approach: The data reported here derive from a qualitative cross-sectional study in one English local authority. The entire study involved interviewing children in care, IROs, social workers and senior managers about young people's participation in their reviews. Findings from the interviews with young people and senior managers have been reported elsewhere (Diaz and Aylward, 2018; Diaz et al., 2018); this paper focusses on the interviews with social workers and IROs. Specifically, the authors were interested in gaining insight into their views about the following research questions: To what degree do children and young people meaningfully participate in reviews? What are the barriers to participation? What can be done to improve children and young people's participation in reviews? Findings: During this process seven themes were identified, five of which concerned barriers to effective participation and two which concerned factors that appeared to support effective participation. These are summarised below and explained further in the following sections. Barriers to effective participation: social workers and IROs' high caseloads and ensuing time pressures; high turnover of social workers and inexperienced staff; lack of understanding and training of professionals in participation; children and young people's negative experiences of reviews and consequent reticence in taking part; and structure and process of the review not being child-centred. Factors which assist participation: quality of the relationship between the child and professionals; and the child or young person chairing their own review meeting. Research limitations/implications: Although these findings reflect practice in one local authority, their consistency with other research in this area suggests that they are applicable more widely. Practical implications: The practice of children chairing their own reviews was pioneered by The Children's Society in North West England in the 1990s (Welsby, 1996), and has more recently been implemented with some success by IROs in Gloucestershire (see Thomas, 2015, p. 47). A key recommendation from this study would be for research to explore how this practice could be developed and embedded more widely. Previous research has noted the tension between the review being viewed as an administrative process and as a vehicle of participation (Pert et al., 2014). This study highlighted practitioner reservations about young people chairing their own reviews, but it also gave examples of how this had been done successfully and how it could improve children's participation in decision making. At the very least, it is essential that young people play a role in deciding where the review is going to take place, when it will take place, who is going to be invited and what will be included on the agenda. Social implications: The paper highlights that in this Local Authority caseloads for social workers were very high and this, combined with a high turnover of staff and an inexperienced workforce, meant that children in care struggled to have a consistent social worker. This often meant that young people were not able to build up a positive working relationship with their social worker, which negatively impacted on their ability to play a meaningful role in decision making. Originality/value: There have been very few recent studies that have considered professionals' perspectives of children's participation in key meetings and decision making, so that this provides a timely and worthwhile contribution to this important area of work.